2023
DOI: 10.1007/s12672-023-00798-w
|View full text |Cite
|
Sign up to set email alerts
|

Synergist for antitumor therapy: Astragalus polysaccharides acting on immune microenvironment

Qian Xu,
Wen Cheng,
Jinrui Wei
et al.

Abstract: Various new treatments are emerging constantly in anti-tumor therapies, including chemotherapy, immunotherapy, and targeted therapy. However, the efficacy is still not satisfactory. Astragalus polysaccharide is an important bioactive component derived from the dry root of Radix astragali. Studies found that astragalus polysaccharides have gained great significance in increasing the sensitivity of anti-tumor treatment, reducing the side effects of anti-tumor treatment, reversing the drug resistance of anti-tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…In a study on C4H/HeJ mouse splenocytes, APS effectively induced B-cell proliferation through a pathway that was not TLR3-dependent. This stimulatory effect was primarily mediated by immunoglobulins on the cell surface, offering new insights into the specific mechanisms by which APS regulates B cells within the immune system [18].…”
Section: Activation and Regulation Of Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on C4H/HeJ mouse splenocytes, APS effectively induced B-cell proliferation through a pathway that was not TLR3-dependent. This stimulatory effect was primarily mediated by immunoglobulins on the cell surface, offering new insights into the specific mechanisms by which APS regulates B cells within the immune system [18].…”
Section: Activation and Regulation Of Immune Cellsmentioning
confidence: 99%
“…It consists of nine monosaccharides, including glucose, galactose, arabinose, and rhamnose, and may contain glucuronic acid and galacturonic acid [16]. Due to its water solubility and low-toxicity characteristics, APS has demonstrated significant biological activities in immune activation and antioxidant, antitumor, antidiabetic, anti-inflammatory, and anti-aging properties; thus, it has great potential for drug discovery in the pharmaceutical and nutraceutical fields [17][18][19][20][21][22][23]. Research indicates that APS is safe and effective for cancer treatment because it enhances the body's immune response, mitigates the side effects of chemotherapy, and activates immune defenses [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, excessive cytokine production aggravates intestine inflammation and intestinal barrier impairment ( 96 ). Interestingly, accumulating evidence reported that APS exerts the potentiality to promote the activities of immune cells (e.g., macrophages, natural killer cells, dendritic cells, T lymphocytes, B lymphocytes, and microglia) and regulates the production of cytokines and chemokines ( 16 , 97 , 98 ). A previous study was conducted to examine the effects of APS ( in ovo injection) on number of immune cells, sIgA, and intestinal immune-related genes expression in broiler chickens.…”
Section: Effects Of Astragalus Polysaccharide On Intestinal Barriermentioning
confidence: 99%
“…It was concluded that ACP activated immune‐related cells and promoted the apoptosis of tumor cells by relying on the mitochondrial pathway to exert the antitumor effects (Zhang et al., 2023). It has been concluded that polysaccharides exert antitumor effects through four main mechanisms: (1) the prevention of tumorigenesis; (2) the inhibition of tumor cell growth, migration, and invasion; (3) the enhancement of immune function; and (4) the induction of apoptosis and cytotoxicity against tumor cells (S. K. Chen, Wang, et al., 2023; Xu et al., 2023).…”
Section: Resources Structures and Functional Properties Of Pnpsmentioning
confidence: 99%